Cooperation of speech pathologists and parents in the organization of correctional work with children with autism syndrome - Usmonjonova Saodatkhan Mirzahamdamovna (Genius Publishing Group, 2024)
This article presents recommendations regarding the cooperation of a speech pathologist with parents of children with autism syndrome. At the same time, the attitude and feelings of the parents of children with autism syndrome towards their child are highlighted, and specific tasks for the speech pathologist in working with them are given and recommendations are made.
Keywords: Autism syndrome; child; correction